Effects of Cognitive Reserve on Cognitive Performance in a Follow-Up Study in Older Adults With Subjective Cognitive Complaints. The Role of Working Memory - Lojo-Seoane, Cristina; Facal, David; Guàrdia-Olmos, Joan; Pereiro, Arturo X.; Juncos-Rabadán, Onésimo (Frontiers in Aging Neuroscience, 2018)
Objective. Analyze the effects of CR on cognitive performance in adults with subjective cognitive complaints at follow-up. Method. We analyzed the factorial structure of the three constructs defined in cognitive performance (Episodic memory, Working memory and General cognitive performance) separately to search for evidence of the invariance of the measurement model. We then developed four structural nested models to analyze the relationship between CR and cognitive performance, measured at baseline and after approximately 18 months, in 266 participants older than 50 years with subjective cognitive complaints. Results. The nested models revealed the following main results: direct effects of CR on all cognitive constructs at baseline and also indirect effects on the same constructs at follow-up, and indirect effects of CR on other cognitive constructs at follow-up via working memory at follow-up. Conclusions. The findings show that the proposed model is useful for measuring the influence of CR on cognitive performance in follow-up studies and that CR has a positive influence on cognitive performance at follow-up via working memory. CR may enhance mechanisms of information processing, favouring performance of tasks involving other cognitive constructs in older adults with subjective cognitive complaints. CR may enhance mechanisms of information processing, favouring performance of tasks involving other cognitive constructs in older adults with subjective cognitive complaints.